2007 Masters Annual (Wiley, 2007)
The Official Commemorative Book Of The 2007 Masters Tournament. Steady Zach Johnson, playing in only his third Masters Tournament, edged out Tiger Woods, Retief Goosen, and Rory Sabbatini by two strokes with a closing 3-under-par 69 to win the title. His 1-over-par 289 tied him with Sam Snead and Jack Burke Jr. for the highest winning score in Masters history. The faith and determination that propelled him through years of playing his way to golf's highest level had taken him to his first Masters victory. Now you can relive all the action of the 2007 Masters, including the thrilling victory by Zach Johnson, who, thanks to a cool head and skillful negotiation of the second nine, won his first Green Jacket. Written from the golfers' perspectives and filled with stunning full-color photographs, the 2007 Masters Annual features revealing stories on the leading participants, a recap of the pre-Tournament Par 3 Contest, and a detailed account of each round as it unfolded, as well as: